Between propaganda and soft power: institutional translation in the Salazar dictatorship - Chumbo, Isabel (2024)
Recent scholarly investigations (Chumbo, 2023; Seruya, 2020) have cast new light on the Salazar dictatorship's perspective on translation during the initial decades of the 20th century. In addition to the customary dissemination of propaganda leaflets and diverse publications, the regime accorded significant importance to political communication executed in foreign languages. These endeavours were predominantly orchestrated through an entity named National Secretariat of Propaganda, especially in the 1930s, the foundational years of the New State regime. As the relatively recent concept of soft power (Nye, 1990; 2004) has found application within the domain of translation studies, it appears relevant to view it applied to this context. Defined as the capacity of a state or individual to influence the preferences of others through an intangible power of attractive communication, this concept is particularly germane to the undertakings of the Portuguese Salazar dictatorship. This regime sought to effectively communicate the values and doctrine of its leader, thereby connecting to the application of soft power principles. This paper directs its attention towards drawing the line between soft power and propaganda within the Portuguese context. Additionally, it aims at providing insight into the institutional performance of the National Secretariat of Propaganda regarding the ideals of the New State. The archival research undertaken for this paper has yielded valuable insights into these inquiries, particularly through the scrutiny of correspondence involving the National Secretariat's governance, editors, publishers, and translators. A meticulous examination of these documents will elucidate the regime's stance and offer conclusions concerning the nature of institutional translation conducted by the central propaganda office. This exploration aims to ascertain whether such actions constituted a mere propaganda exercise or if they were indeed soft power practices designed to project a specific narrative and therefore influence international relations.